1983
DOI: 10.2307/3429585
|View full text |Cite
|
Sign up to set email alerts
|

Determination of 2-Acetylaminofluorene Adducts by Immunoassay

Abstract: Antisera elicited in rabbits were used in radioimmunoassay (RIA) and enzyme-linked immunosorbent assay (ELISA) to determine femtomole quantities of deoxyguanosin-8-yl-acetylaminofluorene (dg-8-AAF) and deoxyguanosin-8-yl-aminofluorene (dg-8-AF). These adducts have been monitored in liver and kidney DNA of male Wistar-Furth rats fed 0.02% or 0.04% 2-acetylaminofluorene (2-AAF) either continuously or for a limited time followed by an interval on control diet. After 24 hr of 0.02% 2-AAF feeding, substantial level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We are not aware of previously published information on the kinetics of formation and elimination of BPDE DNA adducts following a 28-day subchronic repeat dose study in the mouse, however, studies by Poirier et al conducted in rats may help shed some light on murine DNA adduct kinetics. In Poirier et al [ 1982 ], Wistar-Furth rats were fed 2-acetylaminofluorene for 28-days and the kinetics of hepatic DNA adduct formation and elimination were measured. Adduct levels reached a plateau at approximately two weeks, and once treatment stopped, adduct levels began to decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are not aware of previously published information on the kinetics of formation and elimination of BPDE DNA adducts following a 28-day subchronic repeat dose study in the mouse, however, studies by Poirier et al conducted in rats may help shed some light on murine DNA adduct kinetics. In Poirier et al [ 1982 ], Wistar-Furth rats were fed 2-acetylaminofluorene for 28-days and the kinetics of hepatic DNA adduct formation and elimination were measured. Adduct levels reached a plateau at approximately two weeks, and once treatment stopped, adduct levels began to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…Adduct levels reached a plateau at approximately two weeks, and once treatment stopped, adduct levels began to decrease. However, at three-days post-treatment greater than 90% of adducts still remained [Poirier et al, 1982 ]. Based on this information, and the fact that the measured levels of BaP-DNA adducts showed dose-dependency and strong correlation with lacZ mutant frequency, it is safe to say that the BaP-DNA adduct levels at 28 days were at steady state, and the adduct levels measured at 72-hr post-exposure were a sufficiently accurate representation of BaP internal dose.…”
Section: Discussionmentioning
confidence: 99%
“…0006-2960/94/0433-13611 $04.50/0 vivo to a reactive intermediate which then covalently binds to DNA, primarily at the C8 position of guanine (Beland & Kadlubar, 1990;Miller & Miller, 1967;Singer & Grunberger, 1983). A-(Deoxyguanosin-8-yl)-2-aminofluorene DNA adducts (Figure 1) are persistent in mammalian systems (Gupta & Dighe, 1984;Poirier et al, 1982) and have been shown to induce base substitution or frame-shift mutations during DNA replication (Bichara & Fuchs, 1985;Carothers et al, 1993;Mah et al, 1989;Reid et al, 1990), although translesion bypass with correct incorporation of cytosine opposite the modification site is the predominant outcome (Lutgerink et al, 1985;Michaels et al, 1991; Shibutani & Grollman, 1993; van de Poll et al, 1992).…”
mentioning
confidence: 99%
“…oxyguanosin-8-yl)aminofluorene adduct [(AF)G], which is the major and most persistent adduct in mammalian systems (Irving, 1966;Kriek, 1969;Irving & Veazey, 1969;Beland et al, 1982;Poirier et al, 1982).…”
mentioning
confidence: 99%